Task Commitment Program Akselerasi Dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 2 Kota Mojokerto - Achmad Pandu Setiawan (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Gifted children have a unique personality. Generally they have a strong interest in the various fields of interest, are very interested in various moral and ethical issues, very autonomous in making decisions and determining actions. The purpose of this research are: a. To know Task Commitment Acceleration Program (Acceleration) in Learning Islamic Religious Education in SMA Negeri 2 Kota Mojokerto. b. To know the supporting and inhibiting factors of Task Commitment Acceleration Program (Acceleration) in Learning Islamic Religious Education in SMA Negeri 2 Kota Mojokerto. This study uses oriented approach (paradigm) Descriptive-Qualitative, While the type of research is a case study. In this study the researchers themselves are the main data collectors. This research was conducted in SMA Negeri 2 Kota Mojokerto Jl. Ijen No.9, Wates, Magersari, Mojokerto City, East Java 61317 Telephone: (0321) 321505. In this study, the primary data obtained by the researcher is: the results of interviews with the Head of Acceleration Program, teachers of Islamic Education in acceleration classes SMA Negeri 2 Kota Mojokerto. Based on the results of the research, it can be concluded as follows: 1) the teaching and learning activities acceleration program in the subjects of Islamic Religious Education (PAI) in SMA Negeri 2 Kota Mojokerto can not be separated from around: (a) curriculum, acceleration program for curriculum used in such a way (in differentiation), to be completed within 2 years for high school level. As specified in the academic calendar in particular; (b) Learning methods, methods used in learning Islamic Religious Education in acceleration classes include: Classical Methods, Discussion Methods, Sociodrama Methods, Exemplary Methods, Project Methods, and Field Practice Methods; and (c) evaluation system, evaluation in acceleration program is done continuously and continuously to get information about progress and success of student learning. That is the assessment of the results of daily test (sumatif), assessment of the results of general (formative), and National Final Examination (UAN). Especially for the subject of Islamic Religious Education is not included in the Final Examination National. 2) In general, some supporting and inhibiting factors in the implementation of Islamic Religious Education (PAI) learning in acceleration class of SMA Negeri 2 Kota Mojokerto is not much different from the supporting and inhibiting factors in the implementation of Islamic Religious Education learning in regular class.